Juvenile Scleroderma: A Referral Center Experience - Amra ADROVIC,; Sezgin ŞAHİN,; Kenan BARUT,; Özgür KASAPÇOPUR, (Archives of Rheumatology, 2018)
Objectives: This study aims to evaluate the demographic and clinical features, laboratory data, treatment modalities, and outcomes of juvenile systemic sclerosis (JSS) and juvenile localized scleroderma (JLS) patients at a referral pediatric rheumatology center in Turkey. Patients and methods: Medical records of a total of 57 patients, including 29 with JSS (1 male, 28 females; mean age 18.3±3.2 years; range 14 to 27 years) and 28 with JLS (6 males, 22 females; mean age 14.4±4.8 years; range 6 to 23 years), diagnosed betweenJanuary 2006 and Mart 2015 and followed-up for at least six months were evaluated in this retrospective longitudinal study. All medical records were retrospectively analyzed for demographic, clinical, and laboratory findings. Results: Mean age at disease onset was 9.9±4.2 years and 7.7±3.9 years for JSS and JLS, respectively. Mean ages at diagnosis and at the time of study were lower in JLS: 9.1±3.5 years vs. 11.7±3.7 years and 14.4±4.8 years vs. 18.3±3.2 years, respectively. Mean disease duration was 7.8±5.2 years and 8.0±4.3 years for JSS and JLS, respectively. Among JSS patients, interstitial lung disease was seen in eight (27%), pulmonary hypertension in three (10%), and arrhythmia in one (3%). One JSS patient (3%) died as a consequence of cardiac sclerosis. Corticosteroids with methotrexate were used in 29 JSS patients (100%) and in 21 JLS patients (75%). Patients with vasculopathy were treated with nifedipine (n=18, 62%) and bosentan (n=12, 41%). Internal organ involvement was treated with high-dose cyclophosphamide (n=10, 34%) or biological agent (n=3, 10%). Conclusion: Close monitoring of internal organ involvement is of great importance in preventing disease-related complications in JSS and JLS. Although rare, vital organ involvement has a devastating effect on prognosis. Biological agents represent an option for patients resistant to standard immunosuppressive treatment.